Insights Into Design Parameters to Improve Gasketed-plate Heat Exchanger Performance - Mazen M. Abu-Khader (Chemical Engineering Transactions)
The current study presents the effects of various plate parameters, such as; type and plate geometries. Chevron plate characteristics such as chevron angle, port diameter, and channel spacing were presented. The plate fabrication material was also examined based on its thermal conductivity, and the effect of the fluid's physical properties was investigated through an industrial case study. PHEx® software was used as a computational tool to analyse and show each parameter's effect through the simulation of an industrial case study. The selection of the ratio of vertical and horizontal lengths (Lv/Lh) is a key variable in the design and any optimization stage. The varying port diameter is not a viable option for reducing pressure drop. The plate fabrication material, in terms of increasing thermal conductivity, was ineffective in reducing pressure drop but effective in reducing the number of plates. A better understanding of the role of each parameter on the overall exchanger design was achieved to attain the required target in the allowable pressure drop of the exchanger system.